The Results of Re-certification of Reference Standard Sample Used for the Examination of Quality Smallpox Vaccines - A. V. Muhacheva; V. V. Perekrest; A. A. Movsesyants; K. A. Sarkisyan; A. U. Butyrskiy; O. V. Fadeikina; R. A. Volkova; D. V. Shvedov; V. A. Shevtsov (Эпидемиология и вакцинопрофилактика, 2016)
The article presents the results of research quality of drugs for the prevention of smallpox during the period from 2007 to 2015 years, where the reference standard uses industry standard of activity, specificity (identification) and necrotic activity of smallpox vaccine, on indicators: «Specific activity», «The antigenic activity» and «Specific safety». Described research methods, presented results and statistical analysis of the results. The article also provided the results of the regular re-certification of reference standard sample activity, specificity (identification) and necrotic activity smallpox vaccine OOO 42-28-113-12 (ОСО), held in 2015. Branch reference preparation for the determination of activity, specificity and necrotic activity of the smallpox vaccine was re-certified with the « specific activity» assigned value of 4,9 ± 2,7 х 108 pfu/ml. Other certified characteristics were also confirmed. The criteria «Specific activity» and «Specificity (identification)» were determined using chorioallantoic membrane of 12-days-old chicken embryos and compared against the First International reference preparation of the smallpox vaccine. The re-certification of the branch reference preparation for the determination of activity, specificity (identification) and necrotic activity of the smallpox vaccine (42-28-113-12) confirmed the possibility of its further use. The shelf-life before the next re-certification is 3 years.